The features of Nigerian Society in Al-Ilori’s Maqamat: A Descriptive and Analytical Study. صورة المجتمع النيجيري في مقامات الإلوري : دراسة تحليلية وصفية (2016)
This research aims to study cm analyticalcmd descriptive features of Nigerian Society in Sahibu-l- Qur’an al-Ilory 's Maqamah known as "Al- Ilory 's Maqamah ”. Al-Ilory ’s Maqamah is a new production and a virginwork written by Sheikh Muhammad Awwal Abdul Salam knowrt as "Sahibu-l- Qitr'an" in the twenty-firsl Century. Despite the multiplicity of the studies contained in the Maqamah, this research would focus on the study of Nigerian society in Al-Ilory’s Maqamah,Such as; Habits, Traditions, Analyzing the Societal Religion, Literary, Education, Social, Cultural and other fecitures explained by Sahibul-Qur ’an in his Maqamah.